STUDY ON THE EFFECT OF TEMPERATURE ON BIO-ETHANOL PRODUCTION FROM CASSAVA FLOUR AND CASSAVA PEELS: AN INSIGHT INTO BIO-ENERGY PROCESSES - Ekwe, Ogbebor Clara; Akpoveta, Oshevwiyo Vincent; Otedo, Jude Onoriode; Isoje, Abigail Okezi; Afure, Mabel Ajevwaye; Ogonegbu, Augustine Chukwunedum; Otovbo, Ejohwomu Joe; Ogunkola, Elijah (FUDMA JOURNAL OF SCIENCES, 2025)
Knowledge of fermentation parameters with respect to temperature is necessary in bio-ethanol production; as an important process in bio-energy applications for green energy utilization. Bio-ethanol provides an alternative clean energy source that can be obtained from biomass, thereby mitigating pollution problems associated with using environmentally unfriendly energy sources. A study into the effect of temperature on bio-ethanol production from cassava flour and cassava peels was investigated. Temperature was varied between 30-60oC at 5oC intervals and the volume of bio-ethanol produced was examined using optical density measurement. An increase in substrate concentration led to a proportionate increase in the volume of bio-ethanol produced at an optimal temperature of 30oC. However, a gradual decrease in bio-ethanol production was observed beyond 30oC (35-60oC), which shows the effect of temperature on bio-ethanol production from cassava flour and cassava peels, with the yeast activity optimum at 30°C using 80 grams of substrate. The optical density measurements provided a reliable indication of optimum microbial activity and bio-ethanol production. Bio-ethanol yield was higher in cassava flour than in cassava peels at the same concentration, indicating higher carbohydrate content in cassava flour. The findings show a significant temperature influence on the activity of the yeast efficiency in bio-ethanol production. Cassava and its peel are important for the production of bio-ethanol because it holds potential as a valuable feedstock for bio-ethanol production, offering a sustainable solution to waste management and clean energy; therefore, knowledge of the optimal fermentation temperature is an important information in bio-ethanol production from cassava precursors.
Keywords: Bio-ethanol; Cassava peel; Yeast; Cassava flour; Temperature; Optical density